Choosing to coose: reasons and expectations regarding marriage - Alessandra Alves Macedo (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
The choice of the partner in adult life is considered one of the only choices that is made with freedom, however, loaded with social, personal, family expectations and also motivated by subjective aspects (ANTON, 2002). This paper seeks to describe how in the process of choosing the spouse, family aspects are directly or indirectly involved. A semi-structured interview was conducted to seven women in their first year of marriage. Data were analyzed according to Content Analysis. Three categories were chosen: Family of Origin; Marriage; and Religion. The participants have a vision of how their choice was made, with free choice, yet they were influenced by the beliefs and values of the families of origin. In their first year of marriage, they demonstrate good experience in marriage, and have built a relationship based on dialogues, despite the "sayings and no sayings" of the family of origin and society.